2020
DOI: 10.1002/jrsm.1451
|View full text |Cite
|
Sign up to set email alerts
|

How to decide whether a systematic review is stable and not in need of updating: Analysis of Cochrane reviews

Abstract: It is challenging to keep systematic reviews (SR) current and updated. Cochrane designated some of its SRs as "stable," that is, not in need of updating. The issue of stabilizing an SR is an important in research synthesis, because it could help reduce research waste. The aim of this study was to analyze publicly available justifications for stabilizing a Cochrane review, with the ultimate goal of helping to make decisions about whether the update of any SR is warranted. Methods: We analyzed Cochrane reviews l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 12 publications
1
25
0
Order By: Relevance
“…Moreover, a lack of transparency in labeling the Cochrane reviews as stable will likely lead to increased research waste. 4 4.2 | Unclear criteria for deciding that there is enough evidence It has been reported before that few Cochrane protocols, less than 5%, specified analytic methods that would determine that there is enough evidence for stopping updating a review. Both, our earlier study and another report found that the majority of Cochrane reviews were stabilized for reasons other than not having enough evidence.…”
Section: Lack Of Transparent Labeling May Lead To Increased Research ...mentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, a lack of transparency in labeling the Cochrane reviews as stable will likely lead to increased research waste. 4 4.2 | Unclear criteria for deciding that there is enough evidence It has been reported before that few Cochrane protocols, less than 5%, specified analytic methods that would determine that there is enough evidence for stopping updating a review. Both, our earlier study and another report found that the majority of Cochrane reviews were stabilized for reasons other than not having enough evidence.…”
Section: Lack Of Transparent Labeling May Lead To Increased Research ...mentioning
confidence: 99%
“…Both, our earlier study and another report found that the majority of Cochrane reviews were stabilized for reasons other than not having enough evidence. 4,11 However, the research community would benefit from clear criteria (i.e., decision-making algorithms) for conclusiveness of evidence.…”
Section: Lack Of Transparent Labeling May Lead To Increased Research ...mentioning
confidence: 99%
See 2 more Smart Citations
“…WoS and Scopus) used to find articles that provide data to a meta‐analysis, is far from being a mere bureaucratic step (Nakagawa et al, 2007; Gusenbauer & Haddaway, 2020). For example, researchers may avoid wasting time through the repetition of an inclusive meta‐analysis when search strings are reported or may detect the need for a new meta‐analysis when/if the one published was too restrictive (see Babić et al., 2020). However, our results parallel those of Koricheva and Gurevitch, (2014) by showing that only a few studies included full details of bibliographic searches.…”
Section: Discussionmentioning
confidence: 99%